Calcium Electrochemotherapy for Tumor Eradication and the Potential of High-Frequency Nanosecond Protocols - Eivina Radzevičiūtė-Valčiukė; Augustinas Želvys; Eglė Mickevičiūtė; Jovita Gečaitė; Auksė Zinkevičienė; Veronika Malyško-Ptašinskė; Vytautas Kašėta; Jurij Novickij; Tatjana Ivaškienė; Vitalij Novickij (MDPI AG, 2023)
Calcium electroporation (CaEP) is an innovative approach to treating cancer, involving the internalization of supraphysiological amounts of calcium through electroporation, which leads to cell death. CaEP enables the replacement of chemotherapeutics (e.g., bleomycin). Here, we present a standard microsecond (μsCaEP) and novel high-frequency nanosecond protocols for calcium electroporation (nsCaEP) for the elimination of carcinoma tumors in C57BL/6J mice. We show the efficacy of CaEP in eliminating tumors and increasing their survival rates in vivo. The antitumor immune response after the treatment was observed by investigating immune cell populations in tumors, spleens, lymph nodes, and blood, as well as assessing antitumor antibodies. CaEP treatment resulted in an increased percentage of CD4+ and CD8+ central memory T cells and decreased splenic myeloid-derived suppressor cells (MDSC). Moreover, increased levels of antitumor IgG antibodies after CaEP treatment were detected. The experimental results demonstrated that the administration of CaEP led to tumor growth delay, increased survival rates, and stimulated immune response, indicating a potential synergistic relationship between CaEP and immunotherapy.